Pengaruh Motivasi Kerja, Komitmen Organisasi Dan Pengembangan Terhadap Kinerja Pegawai Badan Pengelola Keuangan Dan Aset Kabupaten Serdang Bedagai - Suci Hardiyanti; Sintong Naek Halashon Hutasoit; Sumuntul Martahan H. Sipahutar; Siwan; Uti Pennia; Nilawati Nasti; Neni Sriwahyuni (ARBITRASE: Journal of Economics and Accounting, 2023)
This formula research internal issue is how influence job motivation on employees performance. How influence of organization coomitment xx on employees performance. How influence of    development on employees performance. How influence of    job motivation, organization coomitment, and development  on employees  performance. This research target is to for know influence and analyze of   job motivation on employees performance. For know influence and analyze of organization coomitment on employees performance. For know influence and analyze   development on employees performance. For know influence and analyze job motivation, organization coomitment and development on employees performance. Sample in this research amount to 39 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of job motivation effect positive and significant on employees performance. Organization coomitment effect positive and significant on employees performance. Development effect positive and do not significant on employees performance.  Job motivation, organization coomitment, and development effect and positive and significant on employees performance.